Kesadaran Hukum Masyarakat Kuranji dalam Implementasi Rencana Tata Ruang Wilayah (RTRW) Kota Padang - Beni Saputra; Akmal Akmal; Suryanef Suryanef (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2019)
This research aims to describe the legal awareness of Kuranji people in obeying Spatial Plan of Padang City. This research used qualitative methods with a descriptive analytical approach. This Research conducted in the subdistrict of Kuranji Padang City. The location is chosen because it is one of the agricultural allocation area which is stipulated by Perda No. 4 year 2012 about Spatial Plan of Padang City. The selection of the informant in this study used purposive sampling techniques. Research findings suggest that: 1) the development of Spatial Plan of Padang City in Kuranji sub-district. To control and defend agricultural land, Padang city government is more focused on the approach of law by making regulations that are prohibiting over the function of agricultural land, especially the field of irrigated technical land. 2) The level of public law is still low in implementing Spatial Plan of Padang City, especially in maintaining the existence of food farming land in Kuranji sub-district. 3) Government efforts to foster public law awareness of Spatial Plan of implementation of Padang City in Kuranji sub-district namely: a) conducting socialization, b) Conducting supervision and control, and C) The imposition of incentives and disincentive in Land utilization.